The Mu'adalah Curriculum's Relevance in the Contemporary Society - Mardiana, Dina; Firdaus, Wildani (FALASIFA : Jurnal Studi Keislaman, 2024)
The purpose of this study is to ascertain whether the mu'adalah curriculum still exists in the modern world and what obstacles lie in the way of its implementation following the release of Minister of Religious Affairs Regulation (PMA) number 18 of 2014. The foundation for changes in the educational system, namely the curriculum, is the evolution of art and culture, scientific and technical advancements, and global changes. This is done in order to enable educational establishments, particularly Pesantrens, to adjust and remain competitive in the face of current advancements. In order to gather information and data pertinent to the study topic from a variety of literature sources, including textbooks, scientific journals, theses, and other research reports, this research method employs a qualitative approach with the kind of library research. According to the study's findings, there hasn't been any regression in the existence of Pesantrens to this point. This is due to the government's recognition of Pesantrens through the mu'adalah policy, which was reinforced with the enactment of the Minister of Religious Affairs Regulation (PMA) Number 18 of 2014, enabling Pesantrens to compete on an equal footing with other educational institutions. Of course, there will inevitably be difficulties because of it. Among these, some doubt the caliber of graduates from Mu'adalah Pesantren who choose not to sit for the national exam. Additionally, graduates of the mu'adalah Pesantren occasionally face difficulties showing their diplomas, which can hinder their prospects of getting into college.